Excitatory amino acid antagonists and pentylenetetrazol-induced seizures during ontogenesis. II. The effects of MK-801 - Velísek, L; Veresová, S; Pôbisová, H; Mares, P (Psychopharmacology, 1991)
MK-801 is a non-competitive N-methyl-D-aspartate (NMDA) receptor antagonist with anticonvulsant and neuroprotective properties. The action of MK-801 (0.05-10 mg/kg IP) was assessed against pentylenetetrazol-induced seizures (PTZ; 100 mg/kg SC; 30 min after MK-801) in rats aged 7, 12, 18, 25, and 90 days (N = 263). We observed pronounced ataxia and hypermobility after MK-801 pretreatment during the whole ontogenesis, and the animals exhibited head-weaving and body-rolls. After the combination of MK-801 and PTZ "wet dog shakes" were detected in 18-, 25-, and 90-day-old rats (never seen in controls receiving PTZ only). MK-801 only insignificantly modified the latencies of minimal (clonic) seizures in 18-day-old and older rats where this seizure type is regularly elicited. In 12-day-old rats an increased incidence of minimal seizures was detected. MK-801 nearly completely blocked or strongly delayed major (generalized tonic-clonic) seizures and attenuated the seizure severity during ontogenesis in a dose-dependent manner. Present results suggest the important role of NMDA receptors in the genesis of generalized tonic-clonic seizures whilst the role of NMDA receptors in minimal seizures appears to be negligible during the whole ontogenetic development.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; receptory N-methyl-D-aspartátu; Pentylenetetrazole; záchvaty; Aging; Rats; Male; epilepsie myoklonické; dizocilpinmaleát; Postural Balance; mužské pohlaví; Receptors, N-Methyl-D-Aspartate; Seizures; krysa rodu Rattus; stárnutí; zvířata; Dizocilpine Maleate; Epilepsies, Myoclonic; posturální rovnováha; pentylentetrazol; aminokyseliny; Amino Acids; Animals